2015
DOI: 10.1080/15685551.2014.999466
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-based ionic liquids for free radical photopolymerization

Abstract: Ionic liquid (IL) monomers are receiving increased attention due to their versatile range of application, especially in the electrochemical and electromechanical fields. Within this study, imidazole-based ILs containing a polymerizable methacrylate (MA) group were synthesized to examine their influence on the viscosity and reactivity of typical (meth)acrylates. The IL-MAs were prepared from 1-butylimidazole and bromo methacrylates with different spacer lengths (C 2 -C 6 ). The best results with respect to phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Photoreactivity of ILs consisting of an imidazole ring attached to a methacrylate group through a spacer with variable length (C2–C6) has been studied . With increasing length of the spacer the photopolymerization rate (expressed in mW mg −1 ) decreased.…”
Section: Photopolymerization In Ionic Liquidsmentioning
confidence: 99%
“…Photoreactivity of ILs consisting of an imidazole ring attached to a methacrylate group through a spacer with variable length (C2–C6) has been studied . With increasing length of the spacer the photopolymerization rate (expressed in mW mg −1 ) decreased.…”
Section: Photopolymerization In Ionic Liquidsmentioning
confidence: 99%
“…12 In this context, research interest is growing to explore new versatile ILs in the preparation of novel ionic materials based on the remarkable capabilities of ILs. 13 The ILs based on the imidazolium ring are very adaptable scaffolds that are becoming increasingly popular in a variety of applications including biphasic reaction catalysis, 14 electromechanical actuator membranes, 15 diluents, 16 separation research membranes, 17 and water purification agents, among others. 18 Imidazolium-based ILs were initially introduced in 1984, and since then, interest in their chemistry has exponentially accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the use of these low‐melting ( T m < 100 °C), primarily organic salts stems from their unique properties such as a negligible vapor pressure and a high degree of thermal stability that have lead them to be proposed as alternatives to conventional solvents in a variety of processes . Thermally initiated radical polymerizations of methyl methacrylate (MMA) were some of the first polymerization reactions studied in IL solvents (e.g., 1‐butyl‐3‐methylimidazolium hexafluorophosphate ([C 4 mim][PF 6 ]), and the kinetics of these processes have been extensively investigated for a variety of other monomers and methods of polymerization . Analysis of the rate of propagation ( R p ) using pulsed laser polymerization (PLP) and size exclusion chromatography (SEC) has generally indicated that IL solvation increases propagation rate constants ( k p ) .…”
Section: Introductionmentioning
confidence: 99%